2021
DOI: 10.18527/2500-2236-2021-8-1-1-9
|View full text |Cite
|
Sign up to set email alerts
|

Mutations designed to modify the NS gene mRNA secondary structure affect influenza A pathogenicity in vivo

Abstract: The influenza A virus genome consists of eight segments of negative-sense RNA that encode up to 18 proteins. During the process of viral replication, positive-sense (+)RNA (cRNA) or messenger RNA (mRNA) is synthesized. Today, there is only a partial understanding of the function of several secondary structures within vRNA and cRNA promoters, and splice sites in the M and NS genes. The most precise secondary structure of (+)RNA has been determined for the NS segment of influenza A virus.  The influenza A virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…control the expression of the proteins NS1 and NEP during influenza A infection. 68 RNA secondary structure is inherently ts, and conserved RNA structures (such as, in SARS-CoV-2, the s2m structure, the 3 0 UTR pseudoknot, and the coronavirus packaging signal) may comprise 'RNA thermometers' contributing to the thermal sensitivity of such viruses. 69 Two studies found that temperature affects the balance between transcription and viral replication.…”
Section: Premisementioning
confidence: 99%
See 1 more Smart Citation
“…control the expression of the proteins NS1 and NEP during influenza A infection. 68 RNA secondary structure is inherently ts, and conserved RNA structures (such as, in SARS-CoV-2, the s2m structure, the 3 0 UTR pseudoknot, and the coronavirus packaging signal) may comprise 'RNA thermometers' contributing to the thermal sensitivity of such viruses. 69 Two studies found that temperature affects the balance between transcription and viral replication.…”
Section: Premisementioning
confidence: 99%
“…Virologists tend to focus on mutations that change the sequences of viral proteins. However, RNA secondary structure is known to affect protein expression and has been shown to control the expression of the proteins NS1 and NEP during influenza A infection 68 . RNA secondary structure is inherently ts, and conserved RNA structures (such as, in SARS‐CoV‐2, the s2m structure, the 3′ UTR pseudoknot, and the coronavirus packaging signal) may comprise ‘RNA thermometers’ contributing to the thermal sensitivity of such viruses 69 .…”
Section: The Four Premises Of Temperature Dependent Viral Tropism (Tdvt)mentioning
confidence: 99%